2018
DOI: 10.4103/0973-1482.202886
|View full text |Cite
|
Sign up to set email alerts
|

The effects of thymoquinone and genistein treatment on telomerase activity, apoptosis, angiogenesis, and survival in thyroid cancer cell lines

Abstract: Based on these results, two agents can be good options as potential phytochemotherapeutics against TCCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…In the same research it is also demonstrated that it affects the angiogenesis by acting on NF-κB. Some reports are also available for antiangiogenic activity of TQ with the same VEGF mechanistic activity in different cell lines (Peng et al, 2013, Paramasivam et al, 2012, Kundu et al, 2014, ElKhoely et al, 2015, Ozturk et al, 2018). Inhibition of VEGF not only directly inhibits the angiogenesis but also it causes the necrosis in that particular area of tumor development and in this way it may hamper the blood vessel formation (Ahmad et al, 2019).…”
Section: Thymoquinone and Angiogenesismentioning
confidence: 89%
“…In the same research it is also demonstrated that it affects the angiogenesis by acting on NF-κB. Some reports are also available for antiangiogenic activity of TQ with the same VEGF mechanistic activity in different cell lines (Peng et al, 2013, Paramasivam et al, 2012, Kundu et al, 2014, ElKhoely et al, 2015, Ozturk et al, 2018). Inhibition of VEGF not only directly inhibits the angiogenesis but also it causes the necrosis in that particular area of tumor development and in this way it may hamper the blood vessel formation (Ahmad et al, 2019).…”
Section: Thymoquinone and Angiogenesismentioning
confidence: 89%
“…278 Genistein has also been reported to inhibit glioblastoma, head and neck and other cancers in a telomerase-dependent manner. [279][280][281] In addition, Li et al discovered genistein-induced telomerase repression due to crosstalk between genetic and epigenetic mechanisms. They indicated that genistein decreased the expression of DNA methyltransferases DNMT1, DNMT3a, and DNMT3b, leading to the hypomethylation of the E2F-1 (repressor) recognition site in hTERT and increased binding of E2F-1 and hTERT.…”
Section: Non-oncology Drugs In Drug Repurposingmentioning
confidence: 99%
“…In addition, in vitro invasion assay and gelatin zymography using HSC-3 cells have also shown a decreased expression of VEGF. More recently, using thyroid cancer cells, a group of investigators revealed the downregulation of VEGF-A expression along with human telomerase reverse transcriptase, PTEN, NF-κB, and p21 (Ozturk et al, 2018). All these antiangiogenic molecular mechanistic insights have been summarized in Figure 6 .…”
Section: Molecular Mechanisms Of Action Of Genisteinmentioning
confidence: 99%